Metal compound coating, preparation method thereof and modified bipolar plate
By using pulsed laser deposition and plasma oxygen permeation technology to generate a titanium oxide gradient coating on the surface of the titanium bipolar plate, the problem of degradation of coating protection performance in the composite coating preparation method is solved, and the effect of high corrosion resistance and good conductivity is achieved.
Patent Information
- Application Number
- CN202510146792.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-11
AI Technical Summary
The existing composite coating preparation methods cause interface defects and stress concentration problems between different coatings, resulting in a decrease in the protective performance of the coating, affecting the long-term stability of the coating.
Pulse laser deposition technology and plasma oxygen permeation technology are used to generate titanium nitride oxide coatings with a gradient of oxygen content on the surface of the titanium bipolar plate to form a titanium nitride gradient coating structure to improve the corrosion resistance and conductivity of the coating.
It achieves good conductivity while maintaining high corrosion resistance, reduces corrosion current density and interface contact resistance, and improves the long-term stability and overall performance of the coating.
Smart Images

Figure CN119592987A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water electrolysis devices, bipolar plates and coating materials, and in particular to a metal compound coating and a preparation method thereof and a modified bipolar plate. Background Art
[0002] The full name of proton exchange membrane water electrolysis is Proton Exchange Membrane Water Electrolyzers, or PEMWE for short. Proton exchange membrane, or PEM for short. Proton exchange membrane, or PEM for short. Proton exchange membrane water electrolysis hydrogen production technology has the advantages of fast response speed, low operating temperature, high current density, high hydrogen purity and environmental friendliness. Therefore, PEM water electrolysis hydrogen production technology has attracted much attention in the field of hydrogen energy production. In water electrolysis technology, bipolar plates are key components of PEM water electrolyzers. Their main functions are to collect current, support membrane electrode assemblies, uniformly transmit reaction media, and conduct electricity and heat. Therefore, bipolar plates are required to have certain mechanical strength, good corrosion resistance and thermal conductivity, good machinability and other properties.
[0003] At present, metal bipolar plates have become the first choice for commercial bipolar plates due to their superior mechanical properties. Among them, titanium bipolar plates have good mechanical strength, good processability and good corrosion resistance. However, in the highly corrosive working environment of PEM water electrolyzers, an oxide film is easily formed on the surface of titanium bipolar plates, increasing the interfacial contact resistance between the titanium bipolar plates and the gas diffusion layer; in addition, corrosion of titanium bipolar plates may release metal ions, which may poison the catalyst and proton exchange membrane and affect the life of the electrolyzer.
[0004] At present, the key to improving the performance of titanium bipolar plates lies in the optimization technology of their surface coatings. Researching a coating with both high conductivity and high corrosion resistance to improve the performance of titanium bipolar plates has become the main research direction at present. Traditional coating preparation methods mostly use multi-layer functional layer composite technology, aiming to achieve a comprehensive improvement in corrosion resistance and conductivity by superimposing the functions of different coatings. For example, a patent application with publication number CN114214658A proposes an innovative composite coating preparation method, which uses TA1 pure titanium as the metal bipolar plate substrate, enhances the adhesion of the substrate surface through pretreatment, and then alternately deposits a self-healing layer and a corrosion-resistant layer thereon to form a bottom layer structure with self-repairing ability and strong corrosion resistance. Finally, a conductive layer is deposited on the outermost corrosion-resistant layer to ensure the good conductivity of the bipolar plate.
[0005] However, although this multilayer coating structure can theoretically take into account both corrosion resistance and conductivity, it faces many challenges in practical applications. For example, the performance differences between different coatings may lead to weakened interfacial bonding, which in turn affects the overall stability and service life of the coating. The preparation process of multilayer coatings is complicated and requires precise control of the deposition parameters and thickness of each layer to ensure good matching and synergy between the coatings. In addition, due to the differences in physical and chemical properties between coating materials, there are often problems of interface defects and stress concentration between multilayer coatings. These problems may become a breakthrough for corrosive media erosion, resulting in a decrease in the protective performance of the coating.
[0006] Specifically, the sample prepared by the patent application with publication number CN114214658A, although the corrosion resistance and conductivity of the titanium bipolar plate were improved to a certain extent, its corrosion current density was still as high as 2.5×10 −6 A.cm −2 This value indicates that the coating still has a certain corrosion risk in a long-term, high-load electrolytic environment. Summary of the invention
[0007] In order to solve the problem that the protective performance of the coating is reduced due to interface defects and stress concentration between different coatings in the existing composite coating preparation method, which affects the long-term stability of the coating, the purpose of the present invention is to provide a metal compound coating, a preparation method thereof and a modified bipolar plate.
[0008] To achieve the above objectives, the technical solution of the present invention is as follows.
[0009] A first aspect of the present invention provides a method for preparing a metal compound coating, wherein the metal compound coating is used to coat the surface of a titanium bipolar plate of a water electrolysis device, and the method for preparing the metal compound coating comprises the following steps: Using the titanium bipolar plate of the water electrolysis device as the substrate, a titanium nitride coating is deposited on the surface of the substrate using a pulsed laser deposition process; then a plasma surface oxygen permeation process is used to oxygenate the titanium nitride coating to form a titanium oxynitride coating with a gradient oxygen content.
[0010] The present invention mainly adopts pulsed laser deposition technology and plasma oxygen permeation technology to generate a titanium nitride oxide coating with a gradient oxygen content on the surface of the titanium bipolar plate. While maintaining high corrosion resistance, it also has good conductivity, has no precious metal load, and has low cost. It solves the problem that the protective performance of the coating is reduced due to interface defects and stress concentration between different coatings in the existing composite coating preparation method, affecting the long-term stability of the coating.
[0011] The method of the present invention adopts a plasma oxygen permeation process to form a titanium oxynitride gradient coating structure. The oxygen content changes with the thickness of the coating. The oxygen content on the coating surface is high, and the oxygen content decreases near the titanium substrate, so that the coating can also achieve the effect of both corrosion resistance and conductivity. This is mainly based on the fact that the corrosion resistance of titanium dioxide is better than that of titanium nitride, so the oxygen content is increased on the basis of the titanium nitride coating to improve the corrosion resistance of the titanium oxynitride coating; however, when the oxygen content is too high, it will cause the conductivity of the titanium oxynitride coating to decrease. Therefore, the present invention adopts a plasma oxygen permeation process to form a titanium oxynitride gradient coating structure to improve corrosion resistance while maintaining a certain conductivity.
[0012] Preferably, the oxygen content of the titanium oxynitride coating gradually decreases along the thickness direction as the titanium oxynitride coating approaches the substrate.
[0013] The titanium oxynitride coating of the present invention is a gradient coating, the oxygen content of which changes with the thickness of the coating, the oxygen content on the coating surface is high, and the oxygen content decreases near the titanium substrate.
[0014] Preferably, the thickness of the titanium oxynitride coating with a gradient oxygen content is 240 nm to 300 nm.
[0015] Preferably, the method of depositing a titanium nitride coating on the surface of a substrate using pulsed laser deposition technology comprises the following steps: The pulsed laser deposition process was used, with TiN target as the target material and nitrogen as the working gas. −4 Nitrogen gas is introduced after 400 Pa to form a titanium nitride coating on the surface of the substrate.
[0016] Preferably, the conditions of the pulsed laser deposition process are: The pulse frequency is 8 Hz to 10 Hz, the laser energy is 400 mJ to 450 mJ, the gas pressure of the reaction chamber is 8 Pa to 10 Pa, the deposition temperature is 400° C. to 450° C., and the number of pulse depositions is 12,000 to 16,000 times.
[0017] In the present invention, the titanium nitride coating on the substrate is a continuous and dense metal nitride coating with a golden appearance and a coating thickness of about 300 nm.
[0018] Preferably, the purity of the TiN target is ≥99.9% and the purity of the nitrogen gas is ≥99.9%.
[0019] Preferably, the method for forming a titanium oxynitride coating with a gradient oxygen content comprises the following steps: A plasma surface oxygen permeation process is adopted to introduce oxygen, ionize the oxygen to form oxygen plasma, and then permeate into the titanium nitride coating to form a titanium oxynitride coating with a gradient oxygen content.
[0020] Preferably, the conditions of the plasma surface oxygen permeation process are: The power is 60W, the temperature is 200°C to 400°C, the gas pressure of the reaction chamber is 15Pa to 30Pa, and the oxygen permeation time is 1h to 3h.
[0021] In the plasma oxygen permeation process, the present invention optimizes different process parameters, including oxygen pressure, substrate temperature, oxygen permeation time, etc., to obtain a uniform and dense coating, reduce the influence of surface cracks, and ensure the corrosion resistance of the coating. The self-corrosion current density of the metal compound coating prepared by the present invention can be as high as 6.8×10 −8 A.cm −2 , at a working voltage of 2.0 V, the corrosion current density is less than 1×10 −7 A.cm −2 ;Interface contact resistance is less than 9 mΩ·cm 2 .
[0022] Preferably, before the titanium nitride coating is deposited on the substrate surface by the pulsed laser deposition process, the substrate surface is pre-treated by grinding and polishing to remove the oxide film on the substrate surface to obtain the base material.
[0023] The second aspect of the present invention provides a metal compound coating, which is prepared by the preparation method described in the first aspect.
[0024] Preferably, at an operating voltage of 2.0 V, the corrosion current density of the metal compound coating of the present invention is less than 1×10 −7 A.cm −2 The interfacial contact resistance of the transition metal compound composite coating is less than 9 mΩ·cm 2 .
[0025] The third aspect of the present invention provides a modified bipolar plate, comprising a substrate and a metal compound coating, wherein the substrate is a titanium bipolar plate of a water electrolysis device, and the metal compound coating is the metal compound coating described in the second aspect.
[0026] The modified bipolar plate of the present invention is used in a proton exchange membrane water electrolysis cell, and the metal compound coating described in the second aspect is deposited on the surface of the titanium bipolar plate of the water electrolysis device.
[0027] Beneficial effects of the present invention: 1. The present invention mainly adopts pulsed laser deposition technology and plasma oxygen permeation technology to generate a titanium nitride oxide coating with a gradient oxygen content on the surface of the titanium bipolar plate. While maintaining high corrosion resistance, it also has good electrical conductivity, no precious metal load, and low cost. It solves the problem that the protective performance of the coating is reduced due to interface defects and stress concentration between different coatings in the existing composite coating preparation method, affecting the long-term stability of the coating.
[0028] 2. The method of the present invention adopts a plasma oxygen permeation process to form a titanium oxynitride gradient coating structure. The oxygen content changes with the thickness of the coating. The oxygen content on the coating surface is high, and the oxygen content decreases near the titanium substrate, so that the coating can also achieve the effect of both corrosion resistance and conductivity. This is mainly based on the fact that the corrosion resistance of titanium dioxide is better than that of titanium nitride. Therefore, the oxygen content is increased on the basis of the titanium nitride coating to improve the corrosion resistance of the titanium oxynitride coating; however, when the oxygen content is too high, the conductivity of the titanium oxynitride coating will decrease. Therefore, the present invention adopts a plasma oxygen permeation process to form a titanium oxynitride gradient coating structure to improve corrosion resistance while maintaining a certain conductivity.
[0029] 3. The titanium oxynitride coating prepared by the present invention has better corrosion resistance while maintaining good conductivity, and the coating has good compactness and can provide good protection for the substrate. The best self-corrosion current density of the metal compound coating of the present invention can be 6.8×10 −8 A.cm −2 , compared with the existing technology, it is improved by 1 to 2 orders of magnitude.
[0030] 4. The metal compound coating generated by the present invention has good bonding strength with the titanium substrate and significantly reduces the interface contact resistance between the metal compound coating and the gas diffusion layer. The corrosion current density of the modified bipolar plate of the present invention is less than 1×10 −7 A.cm −2 ;Interface contact resistance is less than 9 mΩ·cm 2 , has good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM image of the cross section of the titanium bipolar plate sample with a titanium oxynitride coating on the surface in Example 1.
[0032] Figure 2 is a SEM image of the titanium oxynitride coating in Example 1.
[0033] Figure 3 Schematic diagram of a titanium nitride coating on the surface of a titanium bipolar plate and a titanium oxynitride coating prepared by a plasma oxygen permeation process in an embodiment of the present invention.
[0034] Figure 4 This is an XPS depth analysis diagram of the cross section of the titanium bipolar plate sample with a titanium oxynitride coating on the surface in Example 1. Among them, 0min to 7min is the XPS stripping time.
[0035] Figure 5 It is a potentiodynamic scanning test diagram of the samples of Example 1, Comparative Example 1 and Comparative Example 2.
[0036] Figure 6 It is the contact resistance test diagram of the samples of Example 1, Comparative Example 1 and Comparative Example 2.
[0037] Figure 7 It is a constant potential scanning test diagram of the samples of Example 1, Example 2 and Comparative Example 1. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0039] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0040] The present invention mainly uses pulsed laser deposition technology and plasma oxygen permeation technology to generate a titanium oxynitride coating with a gradient oxygen content on the surface of the titanium bipolar plate. While maintaining high corrosion resistance, it also has good electrical conductivity, no precious metal load, and low cost. It solves the problem that the existing composite coating preparation method reduces the protective performance of the coating due to interface defects and stress concentration between different coatings, affecting the long-term stability of the coating. The specific preparation method is as follows: A method for preparing a metal compound coating, wherein the metal compound coating is used to cover the surface of a bipolar plate of a water electrolysis device, and the method for preparing the metal compound coating comprises the following steps: Step 1, substrate surface pretreatment: The substrate surface is pretreated by grinding and polishing to remove the oxide film on the substrate surface to obtain a base material.
[0041] Step 2, depositing titanium nitride coating on the surface of titanium substrate: using the bipolar plate of water electrolysis device as substrate, a titanium nitride coating is deposited on the surface of substrate by pulsed laser deposition process. The titanium nitride coating on the substrate is a continuous and dense metal nitride coating with a golden appearance and a coating thickness of about 300nm. The specific method is as follows: The pulsed laser deposition process was used, with TiN target as the target material and nitrogen as the working gas. −4Nitrogen gas is introduced after 400 Pa to form a titanium nitride coating on the surface of the substrate.
[0042] The conditions of the pulse laser deposition process are: pulse frequency of 8Hz~10Hz, laser energy of 400mJ~450mJ, gas pressure of the reaction chamber of 8Pa~10Pa, deposition temperature of 400℃~450℃, pulse deposition times of 12000~16000 times. The purity of TiN target is ≥99.9%. The purity of nitrogen is ≥99.9%.
[0043] Step 3, titanium nitride coating surface oxygenation process: Then use plasma surface oxygenation process to oxygenate the titanium nitride coating to form a titanium oxynitride coating with a gradient oxygen content. The oxygen content of the titanium oxynitride coating is gradually reduced along the thickness direction as it approaches the substrate. The thickness of the titanium oxynitride coating with a gradient oxygen content is 240nm to 300nm. The specific method is as follows: A plasma surface oxygen permeation process is adopted to introduce oxygen, ionize the oxygen to form oxygen plasma, and then permeate into the titanium nitride coating to form a titanium oxynitride coating with a gradient oxygen content.
[0044] The conditions of the plasma surface oxygen permeation process are: temperature of 200°C to 400°C, gas pressure of the reaction chamber of 15Pa to 30Pa, and oxygen permeation time of 1h to 3h.
[0045] The method of the present invention adopts a plasma oxygen permeation process to form a titanium oxynitride gradient coating structure. The oxygen content varies with the coating thickness. The oxygen content is high on the coating surface and decreases near the titanium substrate, so that the coating can also achieve the effects of both corrosion resistance and conductivity.
[0046] In the plasma oxygen permeation process step, the present invention optimizes different process parameters, including oxygen pressure, substrate temperature, oxygen permeation time, etc., to obtain a uniform and dense coating, reduce the influence of surface cracks, and ensure the corrosion resistance of the coating.
[0047] The self-corrosion current density of the metal compound coating prepared by the present invention can be as high as 6.8×10 −8 A.cm −2 , at a working voltage of 2.0 V, the corrosion current density is less than 1×10 −7 A.cm −2 ;Interface contact resistance is less than 9 mΩ·cm 2 .
[0048] The technical solution of the present invention is further described below by means of specific examples. In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0049] Example 1 like Figure 3 A method for preparing a metal compound coating on the surface of a titanium bipolar plate comprises the following steps: S1. Surface pretreatment of titanium substrate: TA1 commercial titanium plate is selected as the titanium substrate, and the TA1 commercial titanium plate is a titanium bipolar plate. SiC sandpaper with a mesh of 1000 to 5000 is used for polishing to remove the oxide film on the surface of the titanium bipolar plate. Then, diamond polishing paste with a particle size of 0.5 µm is used to polish the surface of the titanium substrate into a mirror state. The polished titanium substrate is ultrasonically cleaned with anhydrous ethanol for 30 minutes to remove grease and dirt, and finally naturally air-dried and placed in anhydrous ethanol for standby use.
[0050] S2. Deposition of titanium nitride coating on the surface of titanium substrate: The air-dried titanium substrate was fixed on the sample stage and transferred into the deposition chamber. The substrate was heated to 400°C and the vacuum degree of the chamber was less than 2×10 −4 After reaching 8 Pa, high-purity nitrogen is introduced, and the nitrogen flow rate is adjusted to keep the nitrogen partial pressure at about 8 Pa; the deposition target is set to a 99.9% purity titanium nitride target, the laser frequency is set to 8 Hz, the laser energy is 400 mJ, the pulse number is 16,000 times, and the laser switch is turned on to start depositing the titanium nitride coating; a titanium bipolar plate with a titanium nitride coating on the surface is obtained.
[0051] S3, titanium nitride coating surface oxygen permeation process: the titanium bipolar plate with titanium nitride coating on the surface prepared by pulsed laser deposition process is placed in the reaction chamber of plasma chemical vapor deposition equipment, the substrate temperature is raised to 200 ° C, and the chamber vacuum is less than 1×10 −3 After Pa, oxygen is introduced into the cavity, and the oxygen flow rate is adjusted to keep the oxygen pressure at 15Pa. Then, the RF power is turned on and the power is maintained at 60W. The oxygen is ionized to form plasma, which penetrates into the titanium nitride coating. The oxygen penetration time is maintained at 1h to form a titanium oxynitride coating.
[0052] S4. Turn off the RF power switch, cool naturally to room temperature, and take out the sample from the chamber.
[0053] Example 2 like Figure 3 A method for preparing a metal compound coating on the surface of a titanium bipolar plate comprises the following steps: S1. Surface pretreatment of titanium substrate: TA1 commercial titanium plate is selected as the titanium substrate, and the TA1 commercial titanium plate is a titanium bipolar plate. SiC sandpaper with a mesh of 1000 to 5000 is used for polishing to remove the oxide film on the surface of the titanium bipolar plate. Then, diamond polishing paste with a particle size of 0.5 µm is used to polish the surface of the titanium substrate into a mirror state. The polished titanium substrate is ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally naturally air-dried.
[0054] S2. Deposition of titanium nitride coating on the surface of titanium substrate: The air-dried titanium substrate was fixed on the sample stage and transferred into the deposition chamber. The substrate was heated to 400°C and the vacuum degree of the chamber was less than 2×10 −4 After reaching 8 Pa, high-purity nitrogen is introduced, and the nitrogen flow rate is adjusted to keep the nitrogen partial pressure at about 8 Pa; the deposition target is set to a 99.9% purity titanium nitride target, the laser frequency is set to 8 Hz, the laser energy is 400 mJ, the pulse number is 16,000 times, and the laser switch is turned on to start depositing the titanium nitride coating; a titanium bipolar plate with a titanium nitride coating on the surface is obtained.
[0055] S3, titanium nitride coating surface oxygen permeation process: the titanium bipolar plate with titanium nitride coating on the surface prepared by pulsed laser deposition process is placed in the reaction chamber of plasma chemical vapor deposition equipment, the substrate temperature is raised to 200 ° C, and the chamber vacuum is less than 1×10 −3 After Pa, oxygen is introduced into the cavity, and the oxygen flow rate is adjusted to keep the oxygen pressure at 20Pa. Then, the RF power is turned on and the power is maintained at 60W. The oxygen is ionized to form plasma, which penetrates into the titanium nitride coating. The oxygen penetration time is maintained at 1h to form a titanium oxynitride coating.
[0056] S4. Turn off the RF power switch, cool naturally to room temperature, and take out the sample from the chamber.
[0057] Example 3 like Figure 3 A method for preparing a metal compound coating on the surface of a titanium bipolar plate comprises the following steps: S1. Surface pretreatment of titanium substrate: TA1 commercial titanium plate is selected as the titanium substrate, and the TA1 commercial titanium plate is a titanium bipolar plate. SiC sandpaper with a mesh of 1000 to 5000 is used for polishing to remove the oxide film on the surface of the titanium bipolar plate. Then, diamond polishing paste with a particle size of 0.5 µm is used to polish the surface of the titanium substrate into a mirror state. The polished titanium substrate is ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally naturally air-dried.
[0058] S2. Deposition of titanium nitride coating on the surface of titanium substrate: The air-dried titanium substrate was fixed on the sample stage and transferred into the deposition chamber. The substrate was heated to 400°C and the vacuum degree of the chamber was less than 2×10 −4 After reaching 8 Pa, high-purity nitrogen is introduced, and the nitrogen flow rate is adjusted to keep the nitrogen partial pressure at about 8 Pa; the deposition target is set to a 99.9% purity titanium nitride target, the laser frequency is set to 8 Hz, the laser energy is 400 mJ, the pulse number is 16,000 times, and the laser switch is turned on to start depositing the titanium nitride coating; a titanium bipolar plate with a titanium nitride coating on the surface is obtained.
[0059] S3, titanium nitride coating surface oxygen permeation process: the titanium bipolar plate with titanium nitride coating on the surface prepared by pulsed laser deposition process is placed in the reaction chamber of plasma chemical vapor deposition equipment, the substrate temperature is raised to 200 ° C, and the chamber vacuum is less than 1×10 −3 After Pa, oxygen is introduced into the cavity, and the oxygen flow rate is adjusted to keep the oxygen pressure at 25Pa. Then, the RF power is turned on and the power is maintained at 60W. The oxygen is ionized to form plasma, which penetrates into the titanium nitride coating. The oxygen penetration time is maintained at 1h to form a titanium oxynitride coating.
[0060] S4. Turn off the RF power switch, cool naturally to room temperature, and take out the sample from the chamber.
[0061] Comparative Example 1 TA1 commercial titanium plate without any treatment was used as the titanium bipolar plate sample before modification.
[0062] Comparative Example 2 A method for preparing a metal compound coating on the surface of a titanium bipolar plate, which differs from Example 1 in that the surface of the titanium nitride coating is not treated by a plasma oxygen permeation process, and the specific method comprises the following steps: S1. Surface pretreatment of titanium substrate: TA1 commercial titanium plate is selected as the titanium substrate, and the TA1 commercial titanium plate is a titanium bipolar plate. SiC sandpaper with a mesh of 1000 to 5000 is used for polishing to remove the oxide film on the surface of the titanium bipolar plate. Then, diamond polishing paste with a particle size of 0.5 µm is used to polish the surface of the titanium substrate into a mirror state. The polished titanium substrate is ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally naturally air-dried.
[0063] S2. Deposition of titanium nitride coating on the surface of titanium substrate: The air-dried titanium substrate was fixed on the sample stage and transferred into the deposition chamber. The substrate was heated to 400°C and the vacuum degree of the chamber was less than 2×10 −4 After reaching 8 Pa, high-purity nitrogen is introduced, and the nitrogen flow rate is adjusted to keep the nitrogen partial pressure at about 8 Pa; the deposition target is set to a 99.9% purity titanium nitride target, the laser frequency is set to 8 Hz, the laser energy is 400 mJ, the pulse number is 16,000 times, and the laser switch is turned on to start depositing the titanium nitride coating; a titanium bipolar plate with a titanium nitride coating on the surface is obtained.
[0064] S3. Turn off the laser switch, cool naturally to room temperature, and take out the sample from the chamber.
[0065] Comparative Example 3 A method for preparing a metal compound coating on the surface of a titanium bipolar plate, which differs from Example 1 in that a titanium oxynitride coating is directly deposited on the surface of a titanium substrate, and the specific method comprises the following steps: S1. Surface pretreatment of titanium substrate: TA1 commercial titanium plate is selected as the titanium substrate, and the TA1 commercial titanium plate is a titanium bipolar plate. SiC sandpaper with a mesh size of 1000 to 5000 is used to polish and remove the oxide film on the surface of the titanium bipolar plate, and then a diamond polishing paste with a particle size of 0.5 µm is used to polish the surface of the titanium substrate into a mirror state, and the polished titanium substrate is ultrasonically cleaned with anhydrous ethanol for 30 minutes, and finally naturally air-dried.
[0066] S2. Titanium oxynitride coating is deposited on the surface of titanium substrate: the air-dried titanium substrate is fixed on the sample stage and transferred into the deposition chamber. The substrate is heated to 400°C and the vacuum degree of the chamber is less than 2×10 −4 After 300 Pa, high-purity nitrogen and high-purity oxygen are introduced, and the flow rates of nitrogen and oxygen are adjusted to keep the nitrogen partial pressure at about 8 Pa and the oxygen partial pressure at about 0.2 Pa; the deposition target is set to 99.9% purity titanium nitride target, the laser frequency is set to 8 Hz, the laser energy is 400 mJ, the pulse number is 16000 times, and the laser is turned on to start depositing the titanium oxynitride coating; a titanium bipolar plate with a titanium oxynitride coating on the surface is obtained.
[0067] S3. Turn off the laser switch, cool naturally to room temperature, and take out the sample from the chamber.
[0068] The modified samples of Examples 1 to 3 were used as Sample 1, Sample 2 and Sample 3. The sample before modification of Comparative Example 1 was used as Control Sample 1, the sample after modification of Comparative Example 2 was used as Control Sample 2, and the sample after modification of Comparative Example 3 was used as Control Sample 3. SEM and XPS analysis and corrosion resistance test were performed on the above samples to explore the surface morphology and corrosion resistance of different samples.
[0069] Test 1: SEM and XPS analysis.
[0070] The full name of SEM is Scanning Electron Microscope, and its Chinese name is Scanning Electron Microscope. The full name of XPS is X-ray Photoelectron Spectroscopy, and its Chinese name is X-ray Photoelectron Spectroscopy.
[0071] The titanium oxynitride coating on the surface of the modified sample of Example 1 was analyzed by SEM. The results are as follows: Figure 2 The cross section of the modified sample of Example 1 was subjected to SEM analysis, and the results were as follows: Figure 1 The XPS depth analysis of the modified sample in Example 1 was performed, and the results are as follows Figure 4 shown.
[0072] Depend on Figure 2 It can be seen that the surface of the titanium oxynitride coating prepared in Example 1 is continuous and dense.
[0073] Depend on Figure 1 It can be seen that the titanium oxynitride coating prepared in Example 1 presents a columnar crystal structure with a thickness of about 300 nm.
[0074] Figure 4 The XPS depth analysis results of the modified sample in Example 1 are shown, where 0min to 7min is the XPS stripping time. Figure 4 It can be seen that the titanium oxynitride coating prepared in Example 1 is a gradient coating, and its oxygen content varies with the thickness of the coating. The oxygen content is high on the coating surface and decreases near the titanium substrate.
[0075] Test 2: Corrosion resistance test.
[0076] Potentiodynamic polarization test: The samples before modification in comparative example 1, the samples after modification in examples 1 to 3, and the samples after modification in comparative examples 2 to 3 were respectively subjected to 0.5 M H2SO4 + 0.2 ppm F - Potentiodynamic polarization test was carried out in the solution. Some test results are shown in Figure 5 As shown in Table 1. Generally, the more positive the corrosion potential is and the smaller the corrosion current density is, the smaller the corrosion rate of the material is, that is, the stronger the corrosion resistance of the material is.
[0077] Table 1 Effect of different oxygen pressures in the oxygen permeation process on the performance of the modified titanium bipolar plate
[0078] Note: “-” indicates that no plasma oxygen permeation process was performed.
[0079] Figure 5 The results show that, under the PEMWE simulated working environment, the self-corrosion current density of the TA1 commercial titanium plate sample without any treatment in comparative example 1 is about 1.36×10 −4 A.cm −2 .
[0080] Under the PEMWE simulated working environment, the corrosion current density of the modified sample in Example 1 was reduced to 6.8×10 − 8 A.cm −2 The corrosion potential is -0.21 V. Compared with the sample before modification in Comparative Example 1, the corrosion resistance of the modified sample in Example 1 is greatly improved.
[0081] Under the PEMWE simulated working environment, the corrosion current density of the modified sample in Example 2 was reduced to 4.2×10 −7 A.cm −2, the corrosion potential is -0.37V. Compared with the sample before modification in Example 1, the corrosion resistance of the sample after modification in Example 2 is greatly improved. However, compared with Example 1, the corrosion current density of the sample after modification in Example 2 is still relatively high. This shows that the modification treatment method of Example 1 is more effective in reducing the corrosion rate.
[0082] Under the PEMWE simulated working environment, the corrosion current density of the modified sample in comparative example 3 was reduced to 5.2×10 −8 A.cm −2 , the corrosion potential is -0.30V. Compared with the sample before modification in Comparative Example 1, the corrosion resistance of the modified sample in Comparative Example 3 is greatly improved. The corrosion current density of Comparative Example 3 is similar to that of Example 1, indicating that both have similar effects in reducing the corrosion rate. However, considering the influence of the corrosion potential, that is, the more positive the corrosion potential, the better the corrosion resistance is generally. The corrosion potential of Example 1 is more positive than that of Comparative Example 3, so Example 1 is relatively better in overall corrosion resistance.
[0083] In summary, compared with Comparative Example 2, the modified sample of Example 1 shows better corrosion resistance in terms of corrosion current density and corrosion potential. Compared with Comparative Example 3, although the two are similar in corrosion current density, the corrosion potential of Example 1 is more positive, indicating that the overall corrosion resistance of Example 1 is relatively better. Therefore, under the PEMWE simulated working environment, the modified sample of Example 1 has better corrosion resistance than the modified samples of Comparative Examples 2 and Comparative Examples 3. This may be because the modification method adopted in Example 1 is more effective in reducing the corrosion rate and increasing the corrosion potential.
[0084] Constant potential polarization test: The sample before modification in comparative example 1, the sample after modification in comparative example 2 and the sample after modification in example 1 were respectively subjected to 0.5 M H2SO4 + 0.2 ppm F - A constant potential polarization test was performed at +2V for 6 hours in the solution. The test results are as follows: Figure 7 shown.
[0085] Figure 7 The results show that at a working voltage of 2.0 V, the corrosion current density of the sample before modification in Comparative Example 1 is about 1×10 −4 Acm −2 , corrosion resistance is poor.
[0086] Compared with Comparative Example 1, the modified sample of Comparative Example 2 maintained a relatively smaller corrosion current density in the constant potential test under the PEMWE simulated working environment, which proves that the modified sample of Comparative Example 2 has relatively better corrosion resistance and long-term working stability.
[0087] Compared with Comparative Example 1 and Comparative Example 2, the modified sample of Example 1 maintained a relatively smaller corrosion current density in the constant potential test under the PEMWE simulated working environment, which proves that the modified sample of Example 1 has better corrosion resistance and long-term working stability than the sample before modification of Comparative Example 1 and the sample after modification of Comparative Example 2. This shows that the modification treatment method of Example 1 is more effective in improving corrosion resistance and long-term working stability.
[0088] Interface contact resistance test: In order to evaluate the interface contact resistance characteristics of different samples, the interface contact resistance between the sample before modification in comparative example 1, the samples after modification in comparative examples 2 to 3, and the sample after modification in example 1 were tested respectively. The results are shown in FIG. Figure 6 As shown in Table 1. The full name of interface contact resistance is Interfacial Contact Resistance, referred to as ICR.
[0089] Depend on Figure 6 The results show that the ICR value of the sample before modification in Comparative Example 1 is 34 mΩ·cm 2 .
[0090] After the modification, the ICR value of the modified sample of comparative example 2 was significantly reduced from 34 mΩ·cm before modification. 2 Reduced to 5.4 mΩ·cm 2 This shows that the modification treatment of Comparative Example 2 is effective in improving the interface contact performance.
[0091] However, the ICR value of the modified sample in Comparative Example 3 increased from 34 mΩ·cm 2 Increased to 57.6mΩ·cm 2 This indicates that the modification treatment of Comparative Example 3 did not achieve the expected effect of reducing the ICR value, but increased it.
[0092] In contrast, the ICR value of the modified sample in Example 1 increased from 34 mΩ·cm before modification to 2 Reduced to 8.7 mΩ·cm 2 Although the reduction is not as great as that of comparative example 2, it also shows that the modification treatment has a positive effect on improving the interface contact performance. Moreover, compared with the modified sample of example 1, the ICR value of the modified sample of comparative example 3 is significantly increased, further highlighting the effectiveness of the modification method of example 1.
[0093] In summary, compared with Comparative Examples 1 to 3, the modified sample in Example 1 of the present invention exhibits a more significant effect of reducing the ICR value. This indicates that the modification method used in Example 1 is more effective in improving the contact performance between the sample and the gas diffusion layer or other related interfaces.
[0094] It should be noted that although the modification effect of Comparative Example 2 is also very significant, the corrosion current density of the modified sample of Comparative Example 2 is still higher than that of Example 1, which shows that the modification treatment method of Example 1 is more effective in reducing the corrosion rate. Figure 7 The results further show that the modified sample of Example 1 has better corrosion resistance and long-term working stability than that of Comparative Example 2. This further proves that the modification treatment method of Example 1 is more effective in improving corrosion resistance and long-term working stability than that of Comparative Example 2.
[0095] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a metal compound coating, characterized in that: The metal compound coating is used to cover the surface of the titanium bipolar plate of the water electrolysis device. The preparation method of the metal compound coating comprises the following steps: Using the titanium bipolar plate of the water electrolysis device as the substrate, a titanium nitride coating is deposited on the surface of the substrate using a pulsed laser deposition process; then a plasma surface oxygen permeation process is used to oxygenate the titanium nitride coating to form a titanium oxynitride coating with a gradient oxygen content.
2. The method for preparing the metal compound coating according to claim 1, characterized in that: The oxygen content of the titanium oxynitride coating decreases gradually along the thickness direction as the titanium oxynitride coating approaches the substrate.
3. The method for preparing the metal compound coating according to claim 1, characterized in that: The thickness of the titanium oxynitride coating is 240nm-300nm.
4. The method for preparing the metal compound coating according to claim 1, characterized in that: A method for depositing a titanium nitride coating on a substrate surface using pulsed laser deposition technology comprises the following steps: The pulsed laser deposition process was used, with TiN target as the target material and nitrogen as the working gas. −4 Nitrogen gas is introduced after 400 Pa to form a titanium nitride coating on the surface of the substrate.
5. The method for preparing the metal compound coating according to claim 4, characterized in that: The conditions for the pulsed laser deposition process are: The pulse frequency is 8 Hz to 10 Hz, the laser energy is 400 mJ to 450 mJ, the gas pressure of the reaction chamber is 8 Pa to 10 Pa, the deposition temperature is 400° C. to 450° C., and the number of pulse depositions is 12,000 to 16,000 times.
6. The method for preparing a metal compound coating according to claim 1, characterized in that: A method for forming a titanium oxynitride coating with a gradient oxygen content comprises the following steps: A plasma surface oxygen permeation process is adopted to introduce oxygen, ionize the oxygen to form oxygen plasma, and then permeate into the titanium nitride coating to form a titanium oxynitride coating with a gradient oxygen content.
7. The method for preparing a metal compound coating according to claim 6, characterized in that: The conditions for the plasma surface oxygen permeation process are: The power is 60W, the temperature is 200°C to 400°C, the gas pressure of the reaction chamber is 15Pa to 30Pa, and the oxygen permeation time is 1h to 3h.
8. A metal compound coating, characterized in that: The method is prepared by any one of claims 1 to 7.
9. A modified bipolar plate, characterized in that: It comprises a substrate and a metal compound coating, wherein the substrate is a titanium bipolar plate of a water electrolysis device, and the metal compound coating is the metal compound coating according to claim 8.
Citation Information
Patent Citations
Composite coating for water electrolysis metal bipolar plate and preparation method thereof
CN114214658A
A NiCrAlSi / CeO2 doped YSZ coating on the surface of a gamma-TiAl alloy and a preparing method thereof
CN109207939A
Method for producing photocatalyst material, method for producing material for photoelectric conversion elements, method for producing wear-resistant member, method for producing member for preventing deterioration of edible oils, photocatalyst material, material for photoelectric conversion elements, wear-resistant member, and member for preventing deterioration of edible oils
CN111094626A
Bipolar plate material with TiNxOy coating deposited on surface of stainless steel and preparation method and application of bipolar plate material
CN112144027A
Transition metal compound composite coating as well as preparation method and application thereof
CN118256866A
Cited By
Al-doped transition metal nitride composite coating as well as preparation method and application thereof
CN119843218A
Anode material, preparation method, electrolysis device and application thereof
CN120485836A